THE INFLUENCE OF ORGANIZATIONAL CULTURE, WORK MOTIVATION, LEADERSHIP AND WORK ENVIRONMENT ON THE PERFORMANCE OF KSPPS BMT BIF BINA IHSANUL FIKRI EMPLOYEES IN YOGYAKARTA CITY - Ahmat Nazom Romli; Fitroh Adhilla; Abdul Cholid Hidayat (Universitas Sarjanawiyata Tamansiswa, 2022)
Objectives: this study aims to determine the influence of organizational culture, motivation, leadership, and work environment on the performance of BMT Bina Ihsanul Fikri employees in Yogyakarta. Method: The population in this study was BMT Bina ihsanul fikri employees in Yogyakarta city which amounted to 90 employees and the sample used was 90 employees with a = 0.05 and used the jenih sample method. The data used questionnaires. Analysis tools : Data used multiple regression multiple multiple liniear. The results of the study: the findings of this study show that organizational culture, work motivation, leadership and work environment have a significant effect on the performance of KSPPS BMT Bina Ihsanuk Fikri Yogyakarta employees. Organizational culture has a positive influence on performance. Work motivation has a negative influence on employee performance. Leadership has a positive influence on employee performance. The work environment has a positive influence on employee performance